Shaping our future : challenges for the church in the twenty-first century - Freeman, J. Stephen (Cambridge, Mass : Cowley Publications, 1994)
Papers presented at the Shaping Our Future symposium held in St. Louis, Aug. 1993
Keywords: Pastoral theology -- Episcopal church -- Congresses; Episcopal Church -- Congresses; Mission of the church -- Congresses; Christianity -- Forecasting -- Congresses